Implementasi Controls By The Host State dan Protection For Foreign Investment: Studi Kasus Oleovest Pte.Ltd (Singapura) dengan Pemerintah Indonesia serta Komparasi BIT Indonesia-Singapura Tahun 2005 dengan BIT Indonesia-Singapura Tahun 2018 - Hidayat, Ervira Nurul (LPPM Institut Pendidikan Nusantara Global, 2025)
This study explores the implementation of the concepts of control by the host state and protection for foreign investment by analyzing the dispute between Oleovest Pte. Ltd. and the Government of Indonesia, alongside a comparative analysis of the 2005 and 2018 Indonesia–Singapore Bilateral Investment Treaties (BITs). The core focus lies in the legal and policy tension between the state’s sovereign right to regulate its domestic affairs for public interest and its obligation to provide legal protection and guarantees to foreign investors. This tension is especially significant in investment treaty arbitration, where claims of unfair treatment or indirect expropriation must be balanced against the host state's regulatory authority. The Oleovest case exemplifies this dynamic, with allegations of breaches of fair and equitable treatment (FET) and indirect expropriation raised by the investor, while Indonesia asserts its right to regulate in pursuit of national development and public welfare. The changes between the 2005 and 2018 BITs reflect Indonesia’s evolving approach to balancing investor protection with regulatory autonomy, shifting from broad protections toward clearer exceptions that emphasize the host state’s right to regulate. This study underscores the importance of developing clearer legal frameworks that support both foreign investor confidence and state sovereignty, ensuring that investment treaties remain fair, balanced, and aligned with sustainable development goals.